Youth, Transitional Justice and Art: Documenting War on the Streets of Sana'a, Yemen. (1st April 2022) - Alhariri, Waleed; Al-Alawi, ThiYazen
ABSTRACT: The role and impact of youth and art in war is multifaceted. In this article, presented as a dialogue, Yemeni street artist ThiYazan Al-Alawi shares his views on art, youth and justice in the midst of seven years of civil war in Yemen. His work is part documentation, part memorialization, part analysis, part therapy and part dissent. The artist first reflects on how he started, doing street art around the city, and how protest and war shaped his style and the topics he chose to cover. Al-Alawi explains how art in conflict zones addresses its audience, and how each of his own pieces has a mission. He also discusses recent collaborations with artists abroad which communicate to the outside world what is happening to him and his country. Throughout the dialogue, Al-Alawi gives advice on how the international community should support youth, and how art can be used for social dialogue and accountability. The article also includes selected photos of murals by Al-Alawi and his collaborators.